2000
DOI: 10.1097/00000372-200002000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Phakomatous Choristoma

Abstract: Phakomatous choristoma is a rare congenital lesion of the eyelid that can be clinically and/or histologically mistaken for a cyst, cutaneous adnexal neoplasm, or an ocular adnexal oncocytoma. Only 13 such cases have been previously described, mostly in the English language ophthalmic literature. Zimmerman reported the first case in 1971 and proposed the lesion to be of lenticular anlage origin, a theory that has been widely accepted. We report an additional case occurring in an 8-week-old male infant with a fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Immunohistochemical studies were performed in eight of the reported phakomatous choristomas and revealed positivity for S-100 in all cases [2,3,7,12,13,14,15,16] and positivity for vimentin in seven cases [2,3,7,12,13,14,16]. The here reported case showed the same immunohistochemical results.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Immunohistochemical studies were performed in eight of the reported phakomatous choristomas and revealed positivity for S-100 in all cases [2,3,7,12,13,14,15,16] and positivity for vimentin in seven cases [2,3,7,12,13,14,16]. The here reported case showed the same immunohistochemical results.…”
Section: Discussionsupporting
confidence: 79%
“…The irregularity of the ducts and cords of epithelial cells within the densely fibrotic stroma resembles an infiltrative neoplasm of cutaneous adnexal or lacrimal duct origin [2]. However, the site of involvement, the peculiar basement membrane material and the similarity to "bladder cells" are features that help to distinguish phakomatous choristoma from an infiltrative carcinoma [2]. Immunophenotypically phakomatous choristoma can be distinguished from cutaneous adnexal tumors by positivity for S-100 and vimentin and negative staining for cytokeratin, which would be positive in adnexal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In the 28 published cases, the age at time of surgical excision ranged from 2 weeks to 13 months, with the average being 4.7 months (interquartile range, 2 months–5.5 months). 3–26 There was a slight predominance of PC occurring in males (68%). The mass primarily involved the lower eyelid in 25 cases, with postseptal extension in 16 of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…3–26 It is commonly described as a firm palpable mass presenting at birth, most commonly affecting the lower eyelid nasally with inferomedial orbital extension. 3–26 The table describes the clinical and histological characteristics, management, and outcomes of all published cases in the literature. In the 28 published cases, the age at time of surgical excision ranged from 2 weeks to 13 months, with the average being 4.7 months (interquartile range, 2 months–5.5 months).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation